Characterizing avian pathogenic Escherichia coli (APEC) from colibacillosis cases, 2018 - Darby M. Newman; Nicolle L. Barbieri; Aline L. de Oliveira; Dajour Willis; Lisa K. Nolan; Catherine M. Logue (PeerJ, 2021)
Colibacillosis caused by avian pathogenic Escherichia coli (APEC) is a devastating disease of poultry that results in multi-million-dollar losses annually to the poultry industry. Disease syndromes associated with APEC includes colisepticemia, cellulitis, air sac disease, peritonitis, salpingitis, omphalitis, and osteomyelitis among others. A total of 61 APEC isolates collected during the Fall of 2018 (Aug–Dec) from submitted diagnostic cases of poultry diagnosed with colibacillosis were assessed for the presence of 44 virulence-associated genes, 24 antimicrobial resistance genes and 17 plasmid replicon types. Each isolate was also screened for its ability to form biofilm using the crystal violet assay and antimicrobial susceptibility to 14 antimicrobials using the NARMS panel. Overall, the prevalence of virulence genes ranged from 1.6% to >90% with almost all strains harboring genes that are associated with the ColV plasmid—the defining trait of the APEC pathotype. Overall, 58 strains were able to form biofilms and only three strains formed negligible biofilms. Forty isolates displayed resistance to antimicrobials of the NARMS panel ranging from one to nine agents. This study highlights that current APEC causing disease in poultry possess virulence and resistance traits and form biofilms which could potentially lead to challenges in colibacillosis control.